Implementasi Kebijakan Layanan Pengaduan Masyarakat Secara Online di Dinas Komunikasi dan Informatika Kota Pontianak - Dovvi Dovvi (JPASDEV : Journal of Public Administration and Sociology of Development, 2020)
AbstractThis research entitled The Implementation of Online Public Complaint Service at the Communication and Informatics Office Pontianak City analyzed based on the theory put forward by Edward III. This Research is a type of descriptive from interviews with informants and secondary data obtained from various official documents related to research.The Implementation of Online Public Complaint Service at the Communication and Informatics Office Pontianak City has not been able to run effective due to several factors, namely: 1. Communication, 2 Resource, 3. Disposition, 4. Bureaucratic Structure.Based on these problems, the author can make suggestions, namely: 1. 1. There needs to be an affirmation in the form of rules issued by the regional head, namely the Mayor's regulation, 2. Increase the capacity of the implementers both in quality, 3. Focus on public complaint services and support centralized services in Dinas, Communications and, Informatics, Pontianak City. Key words : The Implementation Policy, Public Complaint Service.